The influence of strategic leadership and planning on the successful implementation of organizational change - Rafiq, Mohammed Ahmed Altaf (2011)
In today’s contemporary business world, characterized by fierce competition and uncertainty, In order to remain competitive, organization must be all set to change. Further, it is significant to note that the influence of the far environment on the organization is irresistible, as such the changes in the external and internal environment tends to dictate the need for change. Implementing this degree of change is intricate in nature. In order to succeed, meticulous planning and strong execution from key personnel are all essential, wherein strategic leadership for implementation and strategic planning constitutes one of the major aspects of successful organizational change. The study covers the strategic organization change, strategic planning and strategic leadership. The strategic planning aligns itself with the strategy to achieve the business objectives and targets set on paper whereas the leadership drives the strategic plan through the diverse situations and risks encountered through various phases of implementation. It also further analyzes the role of human resource management (HRM) for effective implementation of strategic organization change. The study thus focuses on learning and analyzing the role of strategic leadership and the impact of strategic planning on the successful implementation of strategic organization change. The study attempts to find the degree of influence of the role of strategic leadership for implementing strategic organization change. Case study is developed for three leading organizations, conducting interviews for collecting data. The analysis is performed and the results are described revealing the importance and degree of influence of the role of strategic leadership and the impact of strategic planning to achieve successful strategic organization change.